2004
DOI: 10.1128/ec.3.6.1412-1422.2004
|View full text |Cite
|
Sign up to set email alerts
|

FoSTUA, Encoding a Basic Helix-Loop-Helix Protein, Differentially Regulates Development of Three Kinds of Asexual Spores, Macroconidia, Microconidia, and Chlamydospores, in the Fungal Plant PathogenFusarium oxysporum

Abstract: The soil-borne fungus Fusarium oxysporum causes vascular wilt of a wide variety of plant species. F. oxysporum produces three kinds of asexual spores, macroconidia, microconidia, and chlamydospores. Falcate macroconidia are formed generally from terminal phialides on conidiophores and rarely from intercalary phialides on hyphae. Ellipsoidal microconidia are formed from intercalary phialides on hyphae. Globose chlamydospores with thick walls are developed by the modification of hyphal and conidial cells. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
89
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 61 publications
4
89
0
Order By: Relevance
“…Antifungal action of Bacillus metabolites may be due to disruption of fungal cell wall and inhibition of normal conidia development. It is known that chlamydospores with thick walls are developed by the modification of hyphal and conidial cells under unfavorable environmental conditions, such as at low temperature, and these resting bodies act as primary inocula in subsequent soil-borne infections, whereas the microconidia and macroconidia formed by F. oxysporum are important in secondary infection [35] [36]. Minerdi et al [37] reported that microbial symbionts silence the virulence of F. oxysporum and that changes in cell morphogenesis by F. oxysporum underlie this suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Antifungal action of Bacillus metabolites may be due to disruption of fungal cell wall and inhibition of normal conidia development. It is known that chlamydospores with thick walls are developed by the modification of hyphal and conidial cells under unfavorable environmental conditions, such as at low temperature, and these resting bodies act as primary inocula in subsequent soil-borne infections, whereas the microconidia and macroconidia formed by F. oxysporum are important in secondary infection [35] [36]. Minerdi et al [37] reported that microbial symbionts silence the virulence of F. oxysporum and that changes in cell morphogenesis by F. oxysporum underlie this suppression.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of G. cingulata, the stuA deletion mutants failed to infect intact apple fruit due to failure to generate normal turgor pressure within the wild-type-appearing appressorium (33). However, in studies of A. fumigatus and F. oxysporum, the deletion mutant still caused disease (18,21).…”
mentioning
confidence: 99%
“…Similarly, in Aspergillus fumigatus, Fusarium oxysporum, and Glomerella cingulata, deletion of the StuA ortholog resulted in mutants with reduced and abnormal conidiospore formation (18,21,33). In studies of G. cingulata, the stuA deletion mutants failed to infect intact apple fruit due to failure to generate normal turgor pressure within the wild-type-appearing appressorium (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chlamydospores are the third type of spore and are either one or two celled. They are thick-walled spores filled with lipidlike material that serves to carry the fungus when a suitable host is not available, and can remain dormant in soil and infect other hosts for as long as 30 years (1,11,12).…”
Section: Introductionmentioning
confidence: 99%